A Newborn with Infantile-Onset Pompe Disease Improving after Administration of Enzyme Replacement Therapy: Case Report - Bor, Meltem; Ilhan, Ozkan; Gumus, Evren; Ozkan, Solmaz; Karaca, Meryem (Journal of Pediatric Intensive Care, 2020)
Pompe disease (PD) is an autosomal recessive lysosomal storage disorder caused by a deficiency of acid α-1,4-glucosidase enzyme (GAA). PD has two forms, namely the infantile-onset and the late-onset form. In untreated cases, infantile-onset form usually leads to cardio-respiratory failure and death in the first year of life. Herein, we report a newborn with infantile-onset PD characterized by muscular hypotonia, respiratory distress, hypertrophic cardiomyopathy, hepatomegaly, elevated serum enzyme levels of aspartate aminotransferase of 117 IU/L (three times the normal value), alanine aminotransferase of 66 IU/L (1.8 times the normal value), lactate dehydrogenase of 558 IU/L (1.2 times the normal value), and creatine kinase >5,000 IU/L (16 times the normal value). Dried blood spot testing was performed and revealed decreased GAA enzymatic activity (0.07 nmol/mL/h, normal 0.93–7.33 nmol/mL/h). GAA gene analysis performed for confirming the diagnosis showed homozygous mutation c.896T >C (p.Leu299Pro). Initiation of enzyme replacement therapy (ERT) (ERT; 20 mg/kg, once every week) at 28 days of age resulted in weaning off from respiratory support within 1 week after treatment, normalization of cardiac abnormalities, and normal neuromotor development in the 16th month of age. Early diagnosis and early treatment with ERT, especially in the neonatal period, is of great importance to improve cardiac function and motor development in infantile-onset PD.
Keywords: enzyme replacement therapy; hypertrophic cardiomyopathy; infantile-onset Pompe disease; newborn